Determination of Hydrophobic Contact Angle of Epoxy Resin Compound Silicon Rubber and Silica - Abdul SYAKUR; Hermawan Hermawan; Heri SUTANTO (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
Epoxy resin is a thermosetting polymeric material which is very good for application of high voltage outdoor insulator in electrical power system. This material has several advantages, i.e. high dielectric strength, light weight, high mechanical strength, easy to blend with additive, and easy maintenance if compared to that of porcelain and glass outdoor insulators which are commonly used. However, this material also has several disadvantages, i.e. hydrophilic property, very sensitive to aging and easily degraded when there is a flow of contaminants on its surface. The research towards improving the performance of epoxy resin insulation materials were carried out to obtain epoxy resin insulating material with high water repellent properties and high surface tracking to aging. In this work, insulating material was made at room temperature vulcanization, with material composition: Diglycidyl Ether Bisphenol A (DGEBA), Metaphenylene Diamine (MPDA) as hardener with stoichiometric value of unity, and nanosilica mixed with Silicon Rubber (SiR) with 10% (RTV21), 20% (RTV22), 30% (RTV23), 40% (RTV24) and 50% (RTV25) variation. The usage of nanosilica and Silicon Rubber (SIR) as filler was expected to provide hydrophobic properties and was able to increase the value of surface tracking of materials. The performance of the insulator observed were contact angle of hydrophobic surface materials. Tests carried out using Inclined Plane Tracking procedure according to IEC 60-587: 1984 with Ammonium Chloride (NH4Cl) as contaminants flowed using peristaltic pumps. The results show that hydrophobic contact angle can be determined from each sample, and RTV25 has maximum contact angle among others.